Influence of different percentages of seedcoat mottling on the performance of the soybean crop - Almeida, Álvaro Manuel Rodrigues (Pesquisa Agropecuaria Brasileira, 2014)
Seeds from soybean (Glycine max (L.) Merrill) mosaic infected plants very often show seedcoat mottling. Establishing the rates that would be acceptable in seeds for planting purposes has been a problem for the seed producers, research institutions, etc. The objective of this study was to determine the maximum percentage of seedcoat mottling that could be used for planting and still obtain a low level of infected plants and low percentage of seedcoat discoloration at harvesting time. Seed with 0, 10, 20, 40, 80 and 100% of mottling was used for planting two experiments located near Londrina and Maravilha, in Paraná, Brazil. No significant effect was found on seed germination. Virus transmission through the seed was recorded in all, treatments except in the plots sown with non-mottled seeds. Based on yield results and on the quality of the seed produced, it is recommended that planting seed should be as free as possible from seedcoat mottling, but percentages up to 20% are still acceptable if necessary.